Leading Voices in the Denier Choir: Conservative Columnists' Dismissal of Global Warming and Denigration of Climate Science. (June 2013) - Elsasser, Shaun W.; Dunlap, Riley E.
The conservative "echo chamber" is a crucial element of the climate change denial machine. Although social scientists have begun to examine the role of conservative media in the denial campaign, this article reports the first examination of conservative newspaper columnists. Syndicated columnists are very influential because they reach a large audience. We analyze 203 opinion editorials ("op-eds") written by 80 different columnists published from 2007 to 2010, a period that saw a number of crucial events and policy proposals regarding climate change. We focus on the key topics the columnists address and the skeptical arguments they employ. The overall results reveal a highly dismissive view of climate change and critical stance toward climate science among these influential conservative pundits. They play a crucial role in amplifying the denial machine's messages to a broad segment of the American public.